New records of six deep-sea caridean shrimps (Crustacea: Decapoda) from the Ryukyu Islands and its adjacent waters, southwestern Japan - Komai, Tomoyuki; Ohtsuka, Susumu; Yamaguchi, Shuhei; Nakaguchi, Kazumitsu (Zootaxa, 2018)
Six species of caridean shrimps from four families are recorded from Japanese waters for the first time on the basis of material from the Ryukyu Islands and its adjacent waters, collected during research cruises of the T/RV “Toyoshio-maru” of Faculty of Applied Biological Science, Hiroshima University: two species of Crangonidae, Lissosabinea unispinosa Komai, 2006 and Pseudopontophilus serratus Komai, 2004; one species of Oplophoridae, Systellaspis pellucida (Filhol, 1885); one species of Pandalidae, Calipandalus elachys Komai & Chan, 2003; and two species of Pasiphaeidae, Pasiphaea debitusae Hayashi, 1999 and P. gracilis Hayashi, 1999. Of them, L. unispinosa, Pseudopontophilus serratus, Pasiphaea debitusae and P. gracilis are heretofore known from the South-West Pacific localities, and then the geographical ranges of these four species are greatly extended to the north and west. Illustrations and/or colour images are provided for each species to supplement previous descriptions and to give evidence for identification.